2016
DOI: 10.1007/s00018-016-2357-0
|View full text |Cite
|
Sign up to set email alerts
|

Human adenosine deaminases ADA1 and ADA2 bind to different subsets of immune cells

Abstract: At sites of inflammation and tumor growth, the local concentration of extracellular adenosine rapidly increases and plays a role in controlling the immune responses of nearby cells. Adenosine deaminases ADA1 and ADA2 (ADAs) decrease the level of adenosine by converting it to inosine, which serves as a negative feedback mechanism. Mutations in the genes encoding ADAs lead to impaired immune function, which suggests a crucial role for ADAs in immune system regulation. It is not clear why humans and other mammals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 51 publications
2
89
0
2
Order By: Relevance
“…This co‐stimulatory signal leads to augmented production of IFN‐gamma, TNF‐alpha, IL‐6 . In contrast, ADA2 has been found to bind preferentially to neutrophils, CD16 + monocytes, and to less extent to B cells and NK cells . It is secreted by monocytes differentiating into macrophages or dendritic cells and this secretion is down‐regulated by addition of IFN‐gamma .…”
Section: The Human Adenosine Deaminase Enzymes: a Historical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…This co‐stimulatory signal leads to augmented production of IFN‐gamma, TNF‐alpha, IL‐6 . In contrast, ADA2 has been found to bind preferentially to neutrophils, CD16 + monocytes, and to less extent to B cells and NK cells . It is secreted by monocytes differentiating into macrophages or dendritic cells and this secretion is down‐regulated by addition of IFN‐gamma .…”
Section: The Human Adenosine Deaminase Enzymes: a Historical Perspectivementioning
confidence: 99%
“…60 In contrast, ADA2 has been found to bind preferentially to neutrophils, CD16 + monocytes, and to less extent to B cells and NK cells. 62 It is secreted by monocytes differentiating into macrophages or dendritic cells and this secretion is down-regulated by addition of IFNgamma. 32 Moreover, ADA2 but not ADA1 induces T cell-dependent differentiation of monocytes into macrophages and stimulates macrophage proliferation.…”
Section: Ada1 and Ada2: Discrepancies And Similaritiesmentioning
confidence: 99%
“…ADA2 is an enzyme that catalyzes the degradation of adenosine to inosine and is secreted by myeloid cells . The pathomechanism of DADA2 remains unclear, but ADA2 seems to have an immunomodulatory function . While DADA2 is primarily considered a vascular disease of childhood, recent evidence suggests that the clinical spectrum is not limited to vasculitis, arthralgias, and recurrent fevers, but can also include features of autoimmunity and immunodeficiency.…”
mentioning
confidence: 99%
“…is widely distributed in human tissues and is higher in macrophages and lymphoid tissues. It is mediates deamination of the anti-in ammatory nucleoside adenosine to inosine and thus it has a role in maintenance of cellular immunity [9]. It was reported that high serum ADA activities were observed in patients with acute hepatitis, chronic active hepatitis, and in sera and lymphocytes of CL patients [10].…”
Section: Introductionmentioning
confidence: 99%